Rice blast management in Cambodian rice fields using Trichoderma harzianum and a resistant variety - Chou, Cheythyrith; Castilla, Nancy; Hadi, Buyung; Tanaka, Toshiharu; Chiba, Sotaro; Sato, Ikuo (Elsevier, 2020)
Rice blast (Pyricularia oryzae Cavara) is one of the most devastating diseases affecting the rice crop in Cambodia and other countries in the world. The fungus Trichoderma spp. is known as one of biological control agents applied as a soil treatment, seed treatment and foliar application, that is used for suppression of various diseases caused by fungal pathogens. Trichoderma harzianum strain BTB 022 is one of the commercial biological control products available in Cambodian markets. The combined use of T. harzianum and a resistant variety, to manage blast disease, are considered as sustainable approaches to reduce yield losses and to cope with recent restrictions on fungicide use. A series of consecutive experiments was conducted to examine the effectiveness of T. harzianum on suppression of rice blast incidence in Koktrap and Polors agricultural research stations during wet and dry seasons in 2016 and 2017. In both years, the treatments consisted of the use of Trichoderma on susceptible and resistant rice varieties. In 2017 the two treatments were combined with conventional practice treatments representing the average farmers' practice. The experiments were arranged in randomized complete block design with three replications in 2016 and four replications in 2017. Leaf blast incidence was assessed at five and four growth stages in 2016 and 2017, respectively, and the area under the leaf blast progress curve (AULBPC) was computed for each year and location. Neck blast (NB) incidence was assessed at dough stage and grain yield (GY) was measured at ripening stage. T. harzianum reduced the incidence of leaf blast and neck blast on IR504 (susceptible strain), but its efficacy was not consistent. The magnitude of disease suppression by T. harzianum was higher for neck blast than for leaf blast. GY variation was correlated with AULBPC and NB incidence, which suggests that disease reduction corresponded to an increase in yield (AULBPC: r = −0.877, P < 0.001; NB incidence: r = −0.567, P < 0.001). T. harzianum effectively reduced neck blast at high disease pressure. Growing a resistant variety, e.g. CAR14, effectively reduced AULBPC and NB incidence compared to T. harzianum and farmers’ practice of fungicidal use but the association of T. harzianum and resistant variety did not increase the effect in the control of disease